A Combinatorial Approach towards Water‐Stable Metal–Organic Frameworks for Highly Efficient Carbon Dioxide Separation. Issue 10 (14th August 2014) - Hu, Zhigang; Zhang, Kang; Zhang, Mei; Guo, Zhengang; Jiang, Jianwen; Zhao, Dan
Abstract A library of 20 UiO‐66‐derived metal–organic frameworks (MOFs) is synthesized in a combinatorial approach involving mixed ligand copolymerization and two post‐synthetic modifications (PSMs) in tandem. Mixed ligand co‐polymerization of benzene‐1, 4‐dicarboxylic acid (BDC) and sodium 2‐sulfoterephthalate (SS‐BDC) with zirconium tetrachloride (ZrCl4) was used to prepare 5 groups of MOFs with the same UiO‐66 topology but differing amounts of sulfate groups. These MOFs exhibit excellent water stabilities in a pH range of 1 to 12, together with high CO2 uptake capacities and selectivities.